The Transcription Factor ETV1 Induces Atrial Remodeling and Arrhythmia. Issue 5 (17th August 2018) - Rommel, Carolin; Rösner, Stephan; Lother, Achim; Barg, Margareta; Schwaderer, Martin; Gilsbach, Ralf; Bömicke, Timo; Schnick, Tilman; Mayer, Sandra; Doll, Sophia; Hesse, Michael; Kretz, Oliver; et al.
Abstract : Rationale: : Structural and electrophysiological remodeling of the atria are recognized consequences of sustained atrial arrhythmias, such as atrial fibrillation. The identification of underlying key molecules and signaling pathways has been challenging because of the changing cell type composition during structural remodeling of the atria. Objective: : Thus, the aims of our study were (1) to search for transcription factors and downstream target genes, which are involved in atrial structural remodeling, (2) to characterize the significance of the transcription factor ETV1 (E twenty-six variant 1) in atrial remodeling and arrhythmia, and (3) to identify ETV1-dependent gene regulatory networks in atrial cardiac myocytes. Methods and Results: : The transcription factor ETV1 was significantly upregulated in atrial tissue from patients with permanent atrial fibrillation. Mice with cardiac myocyte-specific overexpression of ETV1 under control of the myosin heavy chain promoter developed atrial dilatation, fibrosis, thrombosis, and arrhythmia. Cardiac myocyte-specific ablation of ETV1 in mice did not alter cardiac structure and function at baseline. Treatment with Ang II (angiotensin II) for 2 weeks elicited atrial remodeling and fibrosis in control, but not in ETV1-deficient mice. To identify ETV1-regulated genes, cardiac myocytes were isolated and purified from mouse atrial tissue. Active cis -regulatory elements in mouse atrial cardiac myocytes were identified by chromatin accessibility (assay for transposase-accessible chromatin sequencing) and the active chromatin modification H3K27ac (chromatin immunoprecipitation sequencing). One hundred seventy-eight genes regulated by Ang II in an ETV1-dependent manner were associated with active cis -regulatory elements containing ETV1-binding sites. Various genes involved in Ca 2+ handling or gap junction formation ( Ryr2, Jph2, Gja5 ), potassium channels ( Kcnh2, Kcnk3 ), and genes implicated in atrial fibrillation ( Tbx5 ) were part of this ETV1-driven gene regulatory network. The atrial ETV1-dependent transcriptome in mice showed a significant overlap with the human atrial proteome of patients with permanent atrial fibrillation. Conclusions: : This study identifies ETV1 as an important component in the pathophysiology of atrial remodeling associated with atrial arrhythmias. Abstract : Supplemental Digital Content is available in the text.